2016
DOI: 10.3892/mco.2016.1081
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor necrosis factor-α polymorphism with chemotherapy-induced oral mucositis in patients with esophageal cancer

Abstract: Abstract. The purpose of this study was to evaluate the association between tumor necrosis factor (TNF)-α polymorphisms and oral mucositis (OM) from 5-fluorouracil (5-FU) plus cisplatin (CDDP) chemotherapy for esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…It has been reported in several human studies that the levels of pro-inflammatory cytokines are increased in the blood and saliva of patients during cancer treatment. Other studies using animal models have shown evidence of changes in the serum level and tissue expression of nuclear factor κ-B and the pro-inflammatory cytokines (TNF-α, interleukin (IL)-1β and IL-6) following administration of chemotherapeutic drugs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in several human studies that the levels of pro-inflammatory cytokines are increased in the blood and saliva of patients during cancer treatment. Other studies using animal models have shown evidence of changes in the serum level and tissue expression of nuclear factor κ-B and the pro-inflammatory cytokines (TNF-α, interleukin (IL)-1β and IL-6) following administration of chemotherapeutic drugs [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, only four adopted multivariate analysis. Tumor necrosis factor alpha was reported by two studies, but with different genotypes reported by each study (TT and GG) [33,70]. Single-nucleotide polymorphisms of XRCC1, a gene involved with DNA repair, were reported by two studies [51,81].…”
Section: Predictors Of Oral Mucositismentioning
confidence: 99%
“…Кроме того, генетический полиморфизм может быть про-гностическим маркером развития нежелательных побочных реакций [40], например, ОНП rs1799964 гена TNF-A является прогностическим фактором развития орального мукозита на фоне проводимой химиотерапии у больных раком пищевода [41].…”
Section: гены цитокиновunclassified